Investigation on linear and nonlinear dynamic equation for vehicle model in numerical simulation - Maoqi, Li; M. I., Ishak; P. M., Heerwan (IOP Publishing, 2021)
With the increase in vehicles in the world today, more accidents have occurred. Therefore, more safety systems are needed for conventional vehicles. However, physical testing is dangerous and costly compared with numerical simulation. So, a good numerical simulation is especially important. In general, the vehicle dynamics equations were used in the numerical simulation. There are two types of vehicle dynamics equations that are linear and nonlinear. This paper researched which one is more practical between linear and nonlinear equations in the simulations versus real-time experiments. In this paper, the equation of motion was used to simulate the state of vehicle motion during cornering conditions in the MatLab Simulink software. The results show that the value of the linear and non-linear yaw is close to the yaw from experimental at lower speed conditions. With the speed increase, the linear yaw value will decrease and farther and farther away from experimental yaw results. Although the linear equation is relatively simple to calculate, the results of the nonlinear equations are closer to the results of real experiments. In summary, the nonlinear equation is more applicable, while the linear equation is not applicable to simulate the motion of the vehicle.